THE EFFECTIVENESS OF BUREAUCRACY COMMUNICATION PATTERNS FOR THE COVID TASK IN PUBLIC POLICY IMPLEMENTATION (POST PANDEMIC) - Rina Kurniawati; Nahdi Hadiyanto; Leni Fitriani (DIA: Jurnal Administrasi Publik, 2022)
The impact measures taken to stem the spread of Covid-19 has significantly impacted several areas. Social changes occur in all aspects of people's lives in multiple sectors, both in the economic sector, employment, education, tourism, and the elements of government bureaucracy. However, the handling of the Covid-19 pandemic in the country has shown positive developments. The trend of adding daily cases consistently indicates a decline. This encourages realizing the effectiveness of implementing public policies by the COVID-19 task force with bureaucratic communication patterns for economic recovery after the pandemic. This study uses a descriptive qualitative methodology that uses a literature review to examine and characterize the phenomenon or object of study through social interactions, attitudes, and perceptions of individuals or groups of people. The study results indicate that public services must have service standards and be published as a guarantee of certainty for service recipients, manifested in an effective communication pattern to serve the community. In contrast, the choice of bureaucratic communication patterns such as assertive behavior can be made by direct communication to the needs, desires, and one's opinion without punishing, threatening, or demeaning others. Proactive behavior also involves the rights of others without being too afraid in the process, involving direct expression of one's feelings; this is considering the strategic potential of the Garut district, and the effectiveness of communication patterns in public services is very crucial to be carried out after this pandemic as an economic recovery effort.